Biodegradation of azo dye RO16 in different reactors by immobilized Irpex lacteus - Bolčič Tavčar, Mateja (Acta chimica slovenica, 2006)
Irpex lacteus is a white rot fungus known to decolorize various synthetic dyes. Decolorization of the azo dye Reactive Orange 16 by immobilized culturesof I. lacteus was compared in three different reactor systems of laboratory size: small and large trickle-bed reactors and a rotating-disc reactor. The highest dye decolorization efficiency (90% in 3 days) was observed in the small trickle bed reactor. The production of extracellular ligninolytic enzymes during dye decolorization was measured and the involvement of mycelium-associated activities in the decolorization process assessed. A repeated batch performance test demonstrated the potential of immobilized fungal cultures to decolorize synthetic dyes over long time periods.
Keywords: azo barvila; bioreaktorji; biotechnology; biotehnologija; glive; kapalni reaktor; microbiology; mikrobiologija; mikroorganizmi; razbarvanje; reaktor z rotirajočimi diski